The Differential Role of Central and Bridge Symptoms in Deactivating Psychopathological Networks - Castro, Daniel; Ferreira, Filipa; de Castro, Inês; Rodrigues, Ana Rita; Correia, Marta; Ribeiro, Josefina; Ferreira, Tiago Bento (Frontiers in Psychology, 2019)
The network model of psychopathology suggests that central and bridge symptoms are promising treatment targets because they may accelerate the dissolution of the network of interactions between the symptoms of mental disorders. However, there is no sound theoretical foundation for centrality measures in psychopathological networks and some of them are unstable. The construct of bridge symptoms also lacks a clear definition and diverse conceptualizations coexist in the literature associated with inconsistent methods to identify them. This study explored ModuLand (Kovács et al., 2010) as a conceptually grounded methodological framework to identify bridge symptoms since it distinguishes the two different types of bridge symptoms suggested by previous studies, namely, overlapping and bridging symptoms. A convenience sample of 51 cross-sectional psychopathological networks, published in previous studies addressing diverse mental disorders or clinically relevant problems, were reanalyzed. In order to address the hypothesis that central and bridge symptoms are valuable treatment targets, this study simulated distinct attack conditions on the psychopathological networks by removing symptoms based on their degree and strength centralities, and ModuLand’s measures of bridgeness and overlap. The differential impact of these different symptoms’ characteristics was assessed through the magnitude of the impact and the extent of the attack needed to achieve maximum impact on the number of components, average path lengths, and connectivity. Only moderate evidence to sustain the hypothesis that central symptoms constitute preferential treatment targets were obtained. Results suggest that degree, strength, and bridgeness attack conditions are more effective in the disaggregation of the psychopathological network than the random attack condition only in increasing the number of components of the psychopathological networks. The degree attack condition seemed to perform better than the strength, bridgeness and overlap attack conditions. Bridge symptoms, especially overlapping symptoms, evidenced limited impact on the networks’ disaggregation. The need to address the basic mechanisms underlying the structure and dynamics of the psychopathological networks through the expansion of the current methodological framework and its consolidation in more robust theories is stressed.